Importance of duration and number of ischemic postconditioning cycles in preventing reperfusion mesenteric injuries. Experimental study in rats - Santos,Carlos Henrique Marques dos (2015)
PURPOSE: To evaluate the effect of ischemic postconditioning (IPC) on intestinal mucosa of rats subjected to ischemia and reperfusion process comparing two cycles of reperfusion and ischemia lasting two minutes each and four cycles of reperfusion and ischemia lasting 30 seconds each METHODS: Thirty Wistar rats were distributed into three groups: group A (10 rats), ischemia (30 minutes) and reperfusion (60 minutes); group B (10 rats), ischemia and reperfusion plus IPC by two lasting two minutes each; and Group C (10 rats), ischemia and reperfusion plus IPC by four cycles lasting 30 seconds each. Finally, a segment of small intestine was resected for histological analysis. We analysed the results according to Chiu et al . classification and proceeded to the statistical treatment by Kruskal-Wallis test (p<0.05). RESULTS: The mean degree of tissue injury according to Chiu et al . classification were: Group A, 2.77; in group B, 1.4; and group C, 1.4. B X C (p<0.05). CONCLUSIONS: Ischemic postconditioning was able to minimize reperfusion injury of rats undergone mesenteric ischemia and reperfusion process. There was no difference in the effectiveness of the method comparing two cycles of two minutes with four cycles of 30 seconds by H&E histological evaluation of the ileum after 60-minute reperfusion.